Assessment of Personnel of Machine-Building Corporations of Ukraine and Poland (Economic journal of Lesya Ukrainka Volyn National University, 2018)
The effective functioning of an enterprise depends on the extent of its staff development. Rapid updating of theoretical knowledge, skills and practical skills contributes to raising the professional level of its employees, which is one of the most important factors in ensuring its competitiveness in the market, updating and increasing the volume of production of goods or providing services.The purpose of the work is to estimate the number and cost of personnel of machine-building corporations in Ukraine. The machine-building sector is an important and integral component of the Ukrainian economy. The effectiveness of the functioning of the mechanical engineering enterprises largely determines the production potential of the country, as it is a system-forming sector of the domestic economy.The machine building industry of Ukraine occupies 16,96 % in 2014 in industry, in 2015 it is 16,86 %, in 2016 it will be 17,09 %. In Poland, the share of machine building in industry in 2014 is 16,95 % in 2014 and 17,07 % in 2015. The number of full-time employees working in the machine-building industry in Ukraine and Poland is similar.Thus, a considerable number of workers with a significant share of highly educated specialists are employed in machine building. Indicators of the number of staff employed in engineering in Ukraine and Poland have similar indicators. In Ukraine’s machine-building industry, the spent working time fund is lower than in industry. There is a tendency to increase the cost of personnel for industry and machine building in general.
Keywords: accounting number, corporation, business, evaluation, fund of working time